Anthracnose severity in common bacterial blight in bean under different spacing and plant population - Schuch, Luis Osmar Braga; Antunes, Irajá Ferreira; Ludwig, Marcos Paulo; Oliveira, Sandro de; Lemes, Elisa Souza (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The beans (Phaseolus vulgaris L.) has great economic and social importance in Brazil as part of the basic food. The incidence of leaf diseases cause damage to crops. The objective was to evaluate the severity of Anthracnose and Bacterial blight common in bean under different spacing and plant populations. The experiments were conducted in the experimental area of Agricultural Center of Palma, the Federal University of Pelotas, in three years of cultivation. The populations used were 100, 200, 350 and 500 thousand plants ha-1 with spacings of 25, 50 and 75 cm. The evaluations were conducted in the pods and leaves when the plants were in the R8 stage. During cultivation of the crop the severity of the bacterial blight is higher than in the second crop, whilst the severity of injury is greater in the second crop. The severity of the common bacterial blight and anthracnose varies according to the year of cultivation. Smaller spacings between rows associated with larger populations of plants provide a faster closure of soil which results in a more favorable condition for the development of disease. The uniform distribution of plants in the area reduces disease severity.